2006
DOI: 10.1002/chin.200648036
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Au(II) Catalyst for the Intramolecular exo‐Hydrofunctionalization of Allenes with Carbon, Nitrogen, and Oxygen Nucleophiles.

Abstract: Ring closure reactions O 0130Highly Active Au(II) Catalyst for the Intramolecular exo-Hydrofunctionalization of Allenes with Carbon, Nitrogen, and Oxygen Nucleophiles. -A 1:1 mixture of gold complex AUR and AgOTf is a highly active and selective catalyst for the intramolecular exo-hydroamination of N-allenyl carbamates and for the exo-hydroarylation of 2-allenyl indoles. A 1:1 mixture of AUR and AgOTos is very efficient for the exo-hydroalkoxylation of allenyl alcohols. For all three types of optically active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…These are the catalytic agents in a broad range of transformations at unsaturated carbon centers, primarily alkynes and allenes. Oftentimes a (phosphine)-or (N-heterocyclic carbene)gold(I) cation is formed in situ by halide abstraction with silver(I) reagents (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). An immediate complication is the fate of silver, which itself has a notorious affinity for unsaturated carbon.…”
mentioning
confidence: 99%
“…These are the catalytic agents in a broad range of transformations at unsaturated carbon centers, primarily alkynes and allenes. Oftentimes a (phosphine)-or (N-heterocyclic carbene)gold(I) cation is formed in situ by halide abstraction with silver(I) reagents (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). An immediate complication is the fate of silver, which itself has a notorious affinity for unsaturated carbon.…”
mentioning
confidence: 99%
“…Although mechanistic aspects are not always clarified, activation of multiple bonds with these noble metal complexes, as Lewis acids, by coordination, is proposed in some papers [12][13][14][15][16][17][18]. An example is shown in Scheme 3 [16].…”
Section: Transition Metal Catalysts As Lewis Acidsmentioning
confidence: 97%
“…Many processes have focused on the synthesis of unsaturated 2,5-dihydrofurans as a result of 5-endo-cyclizations from α-hydroxyallenes [127]; however, recent research in the area of gold-catalysis has led to the development of exo-hydroalkoxylations of allenes to form saturated 2-alkenyl-tetrahydrofurans and -tetrahydropyrans. In 2006, Widenhoefer and coworkers reported the use of a Johnphos-gold complex as a catalyst for intramolecular allene hydroalkoxylation which had previously shown efficacy as a catalyst for hydroamination and hydroalkoxylation of alkenes (Scheme 65) [26,93]. It was found that the regioselectivity for hydroalkoxylation of allene 160 was highly dependent on the counterion.…”
Section: Reactions Of Hydroxyallenesmentioning
confidence: 97%
“…Cationic gold complexes are soft Lewis acids that tend to be more carbophilic than oxophilic, which results in increased reactivity for π-activation processes and high functional group tolerance. The development of gold complexes as catalysts for intramolecular hydroaminations of aminoallenes with broad substrate scope was established in 2006 by Widenhoefer and coworkers [93]. This group illustrated that the bulky monophosphine gold catalyst Au[P(t-Bu) 2 (o-biphenyl)]Cl and a cocatalytic amount of AgOTf were highly active for the hydroamination of aminoallenes containing electron-deficient N-donors (i.e., NCbz) (Scheme 47) [93].…”
Section: Gold-and Copper-catalyzed Reactionsmentioning
confidence: 98%
See 1 more Smart Citation